A Ten-year Retrospective Study of Nasal Bone Fractures at a Tertiary Care Hospital of Nepal - Pokharel, Monika; Karki, Subindra; Dhakal, Ashish; KC, Abha Kiran; Shrestha, Krishna Sundar; Rajbhandari, Pradeep; Neupane, Manish (Journal of Lumbini Medical College, 2021)
Introduction: Nasal bone fracture occurs due to its vulnerable position and reduced biomechanical resistance to traumas. If not timely treated, it can result in permanent functional and esthetic damage. Methods: A retrospective and cross-sectional study conducted in 91 patients above 17 years of age with nasal bone fractures in the Department of Otorhinolaryngology and Head and Neck surgery of a tertiary care hospital in Kavre. Results: Road traffic accident was the most common cause of fracture (45.1%) followed by fall (36.3%), violence (13.2%), sports related accidents (4.4%) and occupational accidents (1.1%). Class I fracture was seen in 70 (76.9%), Class II in 17 (18.7%) and Class III in 4 (4.4%). A closed reduction procedure was performed in 74 (81.30%) of the cases, closed reduction with septoplasty was done in 10 (11%), closed reduction with augmentation rhinoplasty was performed for 3 (3.3%), closed reduction with inferior turbinoplasty was required in 3 (3.3%) whereas closed reduction with debridement was done in 1(1.1%). Conclusion: Nasal bone fracture is a complex clinical issue which needs to be addressed early. Violence prevention programs along with drinking and driving campaigns need to be more strengthened to decrease the alarmingly high frequency of nasal bone fracture in the current scenario.